Exploring Educators' Expectations and Experiences of In-Service Education and Training [INSET] as Continuing Professional Development Opportunities - Cheryl le Roux (Environmental Association of Southern Africa, 2005)
In-Service Education and Training (INSET) is widely used to support educators to cope with ongoing changes in education. This paper examines the results of two surveys of INSET recipients' expectations and their experiences of INSET before and after having attended a series of INSET workshops that were held with the intention of strengthening participants' capacity to teach environmental education. The educators who participated in the survey were from three rural districts in the Limpopo Province, a far northern province in South Africa which borders on Zimbabwe. The survey outcomes were appraised against the backdrop of what is identified in the literature as constituting meaningful INSET. The analysis was undertaken to determine the capacity of INSET programmes to realise the presumed goals of INSET. The outcomes of this survey point to a measure of continuity between theory and practice, but also to trends in participants' experiences of INSET that are not predominant in the literature.